Maqāṣid al-Sharī’ah Values in al-Māwardī’s Concept of the Caliphate - Muhamad Fajar Pramono; Amir Sahidin (Al-Ahkam, 2021)
This article aims to reveal the values of maqāṣid al-sharī'ah in al-Māwardī's concept of the caliphate. He emphasizes the relationship between politics and maqāṣid al-sharī'ah, both of which aim to realize the benefit. Through literature study using the descriptive-analytical method, this paper finds that his basic concept of the caliphate is influenced by his understanding of maqāṣid al-sharī'ah, including maqāṣid al-imāmah, wasīlah legal status, and maṣlaḥah rules. All three are criteria and conditions that a leader meets. He succeeded in formulating a series of prerequisites for a leader to realize the benefit of the people. These prerequisites are in line with the substance of maqāṣid al-sharī'ah.